FEASIBILITY INVESTIGATION OF FAULT DIAGNOSIS USING ELECTROMAGNETIC ANALYSIS OF PLANAR STRUCTURES - SOCHEATRA, SOEUNG (2013)
Nowadays, circuit design technologies have progressively advanced to cope with the high performance of the electronic components. With the circuit design advancement,the technology for IC fabrication has moved to deep submicron era. As the circuit sizes continue to scale down to nanoscale, the number of transistors and interconnects on the circuits tends to grow as well. This challengesthe circuit testing by introducing high number of possible faults on the circuit. Consequently, the product qualitycontrol has become more challenging. The product quality could drop significantly ifthe circuits are not designed to be testable.